Deconstructing English Language Learning Facilitation ‎Through A Competency-Based Human Resource Management ‎Perspective In Private Higher Education Institutions - Azmy Muhammad Habiby; Owin Jamasy Jamaluddin; Arham Muhammad Robbani; Andi Suhandi; Wiranta Wiranta (JPI: Jurnal Pustaka Indonesia, 2026)
This study aims to deconstruct the dynamics of English language learning facilitation through a Competency-Based Human Resource Management (HRM) lens at two private higher education institutions in Bekasi, Indonesia: STEBIS YPII Bekasi and Pelita Bangsa University Bekasi. The study responds to the persistence of grammar-dominated English instruction in Indonesian private universities, where classroom practices often prioritize credit-hour completion and administrative compliance over communicative competence development. A qualitative comparative multi-locus case study design was employed. Data were collected through participant observation of classroom facilitation, documentary analysis of Semester Learning Plans (RPS), and in-depth interviews with lecturers as key instructional actors and students as representatives of human capital. Data were analyzed using the interactive thematic analysis model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing. The findings show that both institutions experienced functional instructional stagnation caused by activity-based performance practices that neglected instructional needs assessment, student readiness, and sustainable exit strategies. The transition from teacher-centered instruction to dialogic, learner-centered facilitation helped reduce students’ mental blocks and communication anxiety while strengthening their willingness to participate in English communication activities. From a Competency-Based HRM perspective, dialogic facilitation functions not only as a pedagogical technique but also as a strategic change-management mechanism for transforming lecturer work behavior and improving graduate capacity. However, the study is limited to two private institutions; future research should involve broader institutional contexts and examine the long-term impact of facilitation-based HRM interventions on students’ communicative performance.